The role of selenoproteins in neurodevelopment and neurological function: Implications in autism spectrum disorder - Behl, Supriya; Mehta, Sunil; Pandey, Mukesh K. (Frontiers in Molecular Neuroscience, 2023)
Selenium and selenoproteins play a role in many biological functions, particularly in brain development and function. This review outlines the role of each class of selenoprotein in human brain function. Most selenoproteins play a large antioxidant role within the brain. Autism spectrum disorder (ASD) has been shown to correlate with increased oxidative stress, and the presumption of selenoproteins as key players in ASD etiology are discussed. Further, current literature surrounding selenium in ASD and selenium supplementation studies are reviewed. Finally, perspectives are given for future directions of selenoprotein research in ASD.